Measure the effectiveness of information systems with the naïve bayes classifier method - Agung Triayudi; Sumiati Sumiati; Saleh Dwiyatno; Dentik Karyaningsih; Susilawati Susilawati (Institute of Advanced Engineering and Science, 2021)
Technological advances at this time are developing very fast, information systems became the frontline in technological advancements, the need for information systems to support jobs is increasingly high. However, its implementation for users does not have a significant impact, so that it needs to be reviewed and re-evaluated in the use of the information system built. The naive bayes classifier method can provide